Effect of Dissimilatory Iron Reduction on the Reduction of CH4 Production in Landfill Conditions. (17th March 2019) - Hu, Lifang; Long, Yuyang; Fang, Chengran
Abstract : A high solid anaerobic incubation system was used to study the effect of dissimilatory iron reduction on the inhibition of methanogenesis in a landfill. Different iron sources including FeC6 H5 O7, Fe2 (SO4 )3, Fe2 O3, and Fe 0 were studied. The different iron sources significantly affected the methanogenesis process in the simulated landfill system. FeC6 H5 O7 and Fe2 (SO4 )3 inhibited methanogenesis but Fe 0 and Fe2 O3 increased it. The dissimilatory iron reduction with FeC6 H5 O7 as the iron source demonstrates an anaerobic mineralization process, which enhances the biodegradation but inhibits methanogenesis. The highest rate of reduction of CH4 production (51.9%) was obtained at a dosage rate of 16, 000 mg·kg −1, which corresponded to a reduction of 0.86 g of CH4 per kg of organic matrix. Active inhibition by methanogens using both the hydrogenotrophic and acetoclastic pathways is considered to be the main mechanism underlying the reduction of CH4 production by dissimilatory iron reduction with FeC6 H5 O7 as the iron source. This is the first report on the effect of different iron forms on the reduction of CH4 production during landfilling with organic solid waste.